THE ROLE OF FINANCIAL CONTROL IN GOVERNMENT ORGANIZATIONS - Sattorov Mirjahon Mirzohidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Article state in organizations financial of control role and importance analysis does. Financial control using state budget and resources effective governance, corruption prevent to take and economic stability provision opportunities seeing will be released.